Memphis Belle - Merrick, Monte; Fenton, George; Modine, Matthew; Stoltz, Eric; Donovan, Tate; Sweeney, D. B. (Daniel Bernard) 1961-; Zane, Billy; Astin, Sean; Connick, Harry; Diamond, Reed Edward; Gaines, Courtney; Giuntoli, Neil; et al.
Based on a true story about the famous plane of World War II, the Flying Fortress, Memphis Belle is about the crew of one of the B-17s flying their last mission before they can go home to a hero's welcome.